Deconstructing water sorption isotherms in cement pastes by lattice density functional theory simulations. Issue 8 (24th April 2021) - Zhang, Yao; Liu, Han; Zhao, Cheng; Ju, J. Woody; Bauchy, Mathieu
Abstract: The moisture content in cement pastes influences their mechanical properties and durability. However, the complex, multiscale nature of cement pastes makes it challenging to isolate the contributions of each scale to their macroscopic water sorption isotherms. In particular, the contribution of the calcium–silicate–hydrate gel (the binding phase of cement pastes) remains only partially understood. Here, we introduce a density functional theory lattice model describing water sorption in calcium–silicate–hydrate, which properly reproduces experimental water sorption isotherms in cement pastes. Based on this model, we deconstruct the contribution of each pore scale (interlayer spacing, gel pores, and capillary pores) to the total sorption isotherm. We show that, when the relative humidity is below 80%, the calcium–silicate–hydrate gel accounts for more than 90% of the moisture content adsorbed in cement pastes. In turn, we find that the contribution of the interlayer space within the calcium–silicate–hydrate grains is governed by the competition between the rate of interlayer space opening and the increasing propensity for water to fill larger pores upon increasing relative humidity. Overall, our results highlight the key role played by the calcium–silicate–hydrate in governing the sorption isotherms of cement pastes.